Kemampuan Pseudomonas Kelompok Fluorescens dalam Meningkatkan Ketahanan Tanaman Terung Terhadap Infeksi Virus Mosaik Kuning - Pratama, Septian Aji; Aidawati, Noor; Fitriyanti, Dewi (www.ulm.ac.id, 2023)
Eggplant (Solanum melongena L.) is a native plant known to tropical regions in Indonesia. As an indigenous vegetable, eggplant is almost always found in farmer's markets and traditional markets at relatively cheap prices. Even though eggplant is a vegetable that is popular with the public, it seems that the cultivation of eggplant plants is not as intensive as the cultivation of other favorite vegetable plants such as chilies, tomatoes, onions, and others. The main problem in vegetable cultivation currently being experienced by eggplant farmers in the Ironwood area is the attack of the yellow mosaic virus pathogen. The research used a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications so that there were 20 experimental units. The five treatments given were K- (eggplant control plants without treatment), K+ (eggplant control plants inoculated with yellow virus), P (eggplant plants treated with isolates of the Pseudomonas group flourescens from Palam and inoculated with eggplant yellow virus), B ( Eggplant plants applied with isolates of the Pseudomonas group flourescens from Landasan Ulin and inoculated with eggplant yellow virus), C (Eggplant plants applied with isolates of the Pseudomonas group flourescens from Landasan Ulin and inoculated with eggplant yellow virus). The results of research that have been carried out have concluded that administration of rhizobacteria isolates P, B, and C can induce eggplant plant resistance to eggplant yellow virus infection, but cannot trigger plant height growth.